Animated life cycles of fungi and plants with spores for teaching. Issue 2 (3rd April 2018) - Klees, Guido; Piepenbring, Meike
Abstract: The conveyance of knowledge of the life cycles performed by fungi and plants with spores is a challenge for teaching in university education. The life cycles of fungi, in particular, can be very complex and difficult to understand. This paper presents the development and implementation of a German and English educational software program, including seven animated life cycles of fungi, two animated developments of fungal meiosporangia, and two examples each for ferns, mosses, and algae (cryptogams). We could show that the use of the software supported the study of fungi and spore-producing plants. It was possible to identify attributes of usability that contributed to a high quality of the educational material in concrete teaching situations. Notably, an easy handling of the software and an appropriate amount of information per animation step are crucial. In addition to the didactic insights, the conversations between the animation designers and the mycologist on correct details of developmental processes in the animations lead to interesting questions concerning cell biology. Some of the resulting open questions are at the edge of currently available knowledge, e.g. concerning the transformation of a plasmodium into a high number of small fruiting bodies in myxomycetes or the dikaryotisation of monokaryotic hyphae after spermatisation in rust fungi.